2009
DOI: 10.1177/0022034509337089
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Numerical Aberrations in Oral Lichen Planus

Abstract: The malignant potential of oral lichen planus (OLP) has been a matter of serious controversy. We aimed to detect chromosomal numerical aberrations in cells of brush samples collected from affected mucosa. The samples were simultaneously analyzed for morphology and fluorescent in situ hybridization (FISH) with chromosomes 2 and 8 centromeric probes. We analyzed 57 persons with OLP and 33 control individuals. A cut-off value of aneuploid cells was determined as 1.1%. Aneuploid cells were found in 16 persons with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…Nevertheless, as a noninvasive technique that can augment the clinical examination in predicting the nature of lesions without the need for a biopsy, this method has potentially significant clinical benefits. In the current study and in our previous studies in oral mucosa, [20][21][22] we observed a high correlation between the simultaneous morphology and FISH analysis method and the gold-standard histopathologic diagnosis. Thus, we believe that this method has potential as a powerful tool for clinicians to monitor and follow highrisk patients and can help avoid unnecessary surgical interventions.…”
Section: -41supporting
confidence: 82%
See 4 more Smart Citations
“…Nevertheless, as a noninvasive technique that can augment the clinical examination in predicting the nature of lesions without the need for a biopsy, this method has potentially significant clinical benefits. In the current study and in our previous studies in oral mucosa, [20][21][22] we observed a high correlation between the simultaneous morphology and FISH analysis method and the gold-standard histopathologic diagnosis. Thus, we believe that this method has potential as a powerful tool for clinicians to monitor and follow highrisk patients and can help avoid unnecessary surgical interventions.…”
Section: -41supporting
confidence: 82%
“…[20][21][22] The results also suggested that the presence of numerical aberrations in cells obtained by brush samples predicts the malignant behavior of a suspicious oral lesion. [20][21][22] The objective of the current study was to evaluate the presence of chromosomal numerical aberrations in cells that were collected by noninvasive brush sampling from laryngeal lesions using simultaneous morphologic and FISH analyses. The results were investigated for a correlation with the accepted gold-standard histopathologic diagnosis.…”
mentioning
confidence: 79%
See 3 more Smart Citations